2000
DOI: 10.1289/ehp.00108s4675
|View full text |Cite
|
Sign up to set email alerts
|

Silicosis and coal workers' pneumoconiosis.

Abstract: Exposure to coal mine dust and/or crystalline silica results in pneumoconiosis with initiation and progression of pulmonary fibrosis. This review presents characteristics of simple and complicated coal workers' pneumoconiosis (CWP) as well as pathologic indices of acute and chronic silicosis by summarizing results of in vitro, animal, and human investigations. These results support four basic mechanisms in the etiology of CWP and silicosis: a) direct cytotoxicity of coal dust or silica, resulting in lung cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
179
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(183 citation statements)
references
References 93 publications
2
179
0
2
Order By: Relevance
“…CWP results from exposure to coal mine dust [1]. Although the risk of CWP is associated with the intensity of dust exposure and the total dose, the pathogenesis of CWP remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CWP results from exposure to coal mine dust [1]. Although the risk of CWP is associated with the intensity of dust exposure and the total dose, the pathogenesis of CWP remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Coal workers' pneumoconiosis (CWP) is caused by the chronic inhalation and deposition of coal particles in the lungs [1]. CWP is divided into two categories according to the severity of the disease: simple pneumoconiosis (SP) and complicated pneumoconiosis with progressive massive fibrosis (PMF) [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kachuri et al (2014) indicated that an increasing duration of employment at any concentrations of silica dust exposure was associated with a significantly higher lung cancer risk in Canadian males with odds ratio of 1.76 (95 % CI 1.34-2.31) for ≥30 exposure years adjusted for age, residence, cigarette smoking, and passive smoking. Moreover, excessive and prolonged exposure to silica dust could lead to inflammation in the lung, resulting in pneumoconiosis and progression of pulmonary fibrosis and related lung diseases (Castranova and Vallyathan 2000;Dostert et al 2008;Fubini and Hubbard 2003;Kuroda et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the term silicosis is often inappropriately used in referring to any pneumoconiosis, independently of the actual cause. However, particulates other than silica, such as coal dust, can also produce pneumoconiosis (25).…”
Section: Health Effectsmentioning
confidence: 99%